CLINICAL IMPACT OF DEPRESSION ON TREATMENT OUTCOMES IN RHEUMATOID ARTHRITIS: A LITERATURE REVIEW - Błaszczak, Maciej; Leja, Wiktoria; Latalska, Katarzyna; Zulfiqar, Zeeshan; Kot, Jakub; Czechowicz, Katarzyna; Szczupaj, Maciej; Pastuszak , Andżelika; Borkowski , Konrad; Rudnicki , Jakub (International Journal of Innovative Technologies in Social Science, 2026)
Depression is a common comorbidity in rheumatoid arthritis, however we still don’t know enough about how it affects treatment outcomes. This systematic review aims to assess the clinical influence of depression on disease activity, remission rates, pharmacological treatment response, patient-reported outcomes, and treatment adherence behaviour in individuals with rheumatoid arthritis. A thorough literature review was performed using PubMed, Scopus and Web of Science. We focused on studies published from 2020 to 2026 that evaluated depressive symptoms through validated instruments and reported at least one treatment-related outcome. The results consistently indicated that comorbid depression correlated with greatly elevated composite disease activity scores. It was mostly influenced by subjective rather than objective components. Patients exhibiting depressive symptoms were less likely to attain remission and demonstrated diminished responses to both conventional synthetic and biologic disease-modifying antirheumatic drugs. Depression was also found to be a strong independent predictor of worse health-related quality of life, more pain, more functional disability and less adherence to treatment. These findings underscore the necessity for regular depression screening in rheumatology practice and advocate for the incorporation of mental health interventions into the management of rheumatoid arthritis to enhance treatment outcomes.